The Effect of Various Factors on Variability of Retinal Nerve Fiber Layer Thickness Measurements Using Optical Coherence Tomography - Youm, Dong Ju (The Korean Ophthalmological Society, 2012)
PURPOSE: To evaluate the effects of various factors on the variability of retinal nerve fiber layer (RNFL) thickness measurements using the Stratus optical coherence tomography (OCT) in normal and glaucomatous eyes. METHODS: Four hundred seventy-four subjects (103 normal eyes and 371 glaucomatous eyes) were scanned to determine the RNFL thickness measurements using the Stratus OCT. Measurements were obtained twice during the same day. The standard deviation (SD) was used to compare the variability in RNFL thickness measurements of the normal subjects to that of the glaucomatous patients. Multivariate regression analysis was used to evaluate which covariates were independent predictors of SD in overall mean RNFL thickness. RESULTS: The mean SD of all RNFL thickness measurements was larger in the glaucoma group except in one sector. In the multivariate regression analysis, the average signal strength (SS) and the relative SS change (difference in SS between initial and repeat scans, divided by initial SS) were independent predictors of the SD in the RNFL thickness measurements (partial R(2) = 0.018, 0.013; p = 0.016, 0.040, respectively). CONCLUSIONS: Glaucomatous eyes tend to be more variable than normal eyes in RNFL thickness measurement using the Straus OCT. The average SS and the relative SS changes appear to correlate with the variability in RNFL thickness measurement. Therefore, the results of the RNFL analysis should not be interpreted independently of these factors.